Is tagging with visual implant elastomer a reliable technique for marking earthworms? - Butt, Kevin Richard; Briones, Maria Jesús Iglesias; Lowe, Christopher (Pesquisa Agropecuaria Brasileira, 2010)
Visual implant elastomer (VIE) has recently been employed to investigate different aspects of earthworm ecology. However, a number of fundamental questions relating to the detection and positioning of the tag, its persistence and potential effects on earthworms remain unknown. Seven earthworm species belonging to three ecological groupings, with different pigmentation and burrowing behaviour, were tagged using different coloured VIE. External inspection after two days, one week and 1, 10 and 27 months were followed by preservation, dissection and internal inspection. Tags could be seen in living specimens to 27 months, and dissection revealed that in most cases they were lodged in the coelomic cavity, held in place by septa. However, over longer time periods (more than two years), the chlorogogenous tissue tended to bind to the tags and made external observation increasingly difficult. Migration of the VIE material towards the posterior of the earthworm and potential loss of the tag were only observed on rare occasions, and a recovery rate in excess of 98% was recorded. By introducing a reasonable amount of VIE into segments, just after the clitellum, this technique can become a valuable tool in earthworm ecology and life history studies, particularly in short-medium term laboratory and field experiments.